“STUDENTS' PERCEPTIONS OF THE USE OF LCD PROJECTORS AS ENGLISH LEARNING MEDIA: A CASE STUDY IN A OF THE PRIVATE HIGH SCHOOLS IN WEST SUMATRA” - Febry Anisa Putri; Edwar Kemal; Herfyna Asty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students' perceptions of the use of LCD projectors as a medium for teaching English at MTs TI Koto Tuo Kumpulan, a private religious school in West Sumatra. The use of technology in learning is considered important for improving the quality of the teaching and learning process, but its implementation in some schools still faces various obstacles. This study uses a quantitative descriptive approach involving seventh-grade students who have been learning English using LCD projectors since 2024. Data were collected through a closed questionnaire using a Likert scale that measured the aspects of usefulness, ease of understanding, attractiveness and engagement, as well as challenges or shortcomings in the use of LCD projectors. The data obtained were analyzed using descriptive statistics in the form of frequency, percentage, mean, and standard deviation. The results showed that, in general, students had a positive perception of the use of LCD projectors in English language learning. This media was considered to be able to help students understand the material, increase their motivation to learn, attract their attention, and make learning more interesting and enjoyable. However, there are still several obstacles, such as technical problems, classroom lighting conditions, and the potential for boredom if its use is monotonous. Overall, LCD projectors can be concluded to be an effective learning medium when used appropriately and in a variety of ways. Therefore, it is recommended that schools provide adequate facilities and provide ongoing training to teachers to optimize the use of technology-based learning media.